Determination of in vitro immunotoxic potencies of a series of perfluoralkylsubstances (PFASs) in human Namalwa B lymphocyte and human Jurkat T lymphocyte cells - Janssen, Aafke W. F.; Jansen Holleboom, Wendy; Rijkers, Deborah; Louisse, Jochem; Hoekstra, Sjoerdtje A.; Schild, Sanne; Vrolijk, Misha F.; Hoogenboom, Ron L. A. P.; Beekmann, Karsten (Frontiers in Toxicology, 2024)
Exposure to PFASs is associated to several adverse health effects, such as immunotoxicity. Immunotoxic effects of PFOA and PFOS, including a reduced antibody response in both experimental animals and humans, have been reported. However, there is limited understanding of the underlying mechanisms involved. Moreover, there is only a restricted amount of immunotoxicity data available for a limited number of PFASs. In the current study the effects of 15 PFASs, including short- and long-chain perfluorinated carboxylic and sulfonic acids, fluorotelomer alcohols, and perfluoralkyl ether carboxylic acids were studied on the expression of recombinant activating gene 1 (RAG1) and RAG2 in the Namalwa human B lymphoma cell line, and on the human IL-2 promotor activity in Jurkat T-cells. Concentration-response data were subsequently used to derive in vitro relative potencies through benchmark dose analysis. In vitro relative potency factors (RPFs) were obtained for 6 and 9 PFASs based on their effect on RAG1 and RAG2 gene expression in Namalwa B-cells, respectively, and for 10 PFASs based on their inhibitory effect on IL-2 promotor activity in Jurkat T-cells. The most potent substances were HFPO-TA for the reduction of RAG1 and RAG2 gene expression in Namalwa cells (RPFs of 2.1 and 2.3 respectively), and PFDA on IL-2 promoter activity (RPF of 9.1). RAG1 and RAG2 play a crucial role in V (D)J gene recombination, a process for acquiring a varied array of antibodies crucial for antigen recognition. Hence, the effects observed in Namalwa cells might indicate a PFAS-induced impairment of generating a diverse range of B-cells essential for antigen recognition. The observed outcomes in the Jurkat T-cells suggest a possible PFAS-induced reduction of T-cell activation, which may contribute to a decline in the T-cell dependent antibody response. Altogether, the present study provides potential mechanistic insights into the reported PFAS-induced decreased antibody response. Additionally, the presented in vitro models may represent useful tools for assessing the immunotoxic potential of PFASs and prioritization for further risk assessment.